Meta-Analysis on the Chinese Herbal Formula Xiaoer-Feike Granules as a Complementary Therapy for Children With Acute Lower Respiratory Infections - You, Qiang; Li, Lan; Li, Dan; Yang, Dan; Chen, Lin; Chen, Hong-ping; Liu, You-ping (Frontiers in Pharmacology, 2020)
Background: Chinese herbal formula (CHF) Xiaoer-Feike granules (XFG) has been widely used as adjuvant therapy for acute lower respiratory infection (ALRI) in recent five years. Considering the rapid popularization and application of XFG, and no systematic evidence evaluate the effectiveness and safety of XFG in treating ALRL, therefore, it is necessary to conduct a meta-analysis to determine whether additional XFG can bring more benefits to patients with ALRI. Methods: Randomized controlled trials (RCTs) of XFG treatment for ALRI through July, 2019 were systematically identified in 4 English databases (PubMed, Cochrane Library, Ovid and Web of Science) and 4 Chinese databases (Chinese Biomedical, China National Knowledge Infrastructure, China Science and Technology Journal Database, and Wan-Fang). Quality assessment and data analysis were performed by Review Manager 5.3.5 and Stata 15.1 Results: 21 RCTs involving 3425 patients were randomly divided into XFG group and conventional medicine (CM) group. The results showed that the clinical efficacy rate (CER) of the XFG group was significantly higher than that of the CM group (OR=3.74, 95% CI =2.95–4.74, P< 0.00001). In comparison with the CM group, the resolution time of cough (RTC) (MD = −1.92; 95% CI =−2.33, -1.51, P<0.00001), resolution time of rale (RTR) (MD = −1.68; 95% CI =−2.27, -1.10, P<0.00001), resolution time of fever (RTF) (MD = −1.46; 95% CI =−1.92, -1.00, P<0.00001), resolution time of inflammatory lesions (RTIL) (MD = -2.43, 95% CI =-2.94, -1.93, P< 0.00001) and hospital stays (HS) (MD = -2.26, 95% CI =-3.03, -1.49, P< 0.00001) of the XFG group were strikingly shortened. At the cellular and molecular level, the CD4, CD8, CD4/CD8, IL-6, TNF-α and CRP levels were significantly improved when complemented with XFG. In addition, no statistic difference was observed between the XFG and CM group in terms of the adverse events (OR=0.97, 95% CI =0.59-1.59, P=0.89). Conclusions: XFG could be recommended as an effective and safe complementary therapy for the treatment of ALRI. Moreover, long-term and higher quality of RCTs are needed to provide strong evidence to overcome the limitations of the selected studies and more precisely interrogate the efficacy and safety of XFG.